2021
DOI: 10.1186/s12948-021-00142-z
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin in mugwort cross-reacts to house dust mite, eliciting non-Th2 response in allergic rhinitis patients sensitized to house dust mite

Abstract: Background Mugwort and house dust mite (HDM) are two of the most common inhalant allergens in Asia, however, whether mugwort affects polysensitized HDM+ allergic rhinitis (AR) patients has not been elucidated. Methods Overall, 15,884 AR outpatients were assessed for clinical status. Amino acid sequences of mugwort were determined by mass spectrometry. Afterward, cross-reactivity between mugwort tropomyosin and Dermatophagoides pteronyssinus 10 (Der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The structure and sequence similarity of TM is the foundation of cross‐reactivity among different arthropod species. The high homology in the sequence is up to 98% among crustacean TMs, and 68%−100% among molluskan TMs (Duan et al., 2021; Palmer et al., 2020; Prester, 2016). Similarly, the high homology in the sequence is 80%−97% among crustaceans and house dust mite TMs and 78%−98% among crustacean and cockroach TMs.…”
Section: Tm: Molecular Characterization Epitopes and Cross‐reactivitymentioning
confidence: 99%
“…The structure and sequence similarity of TM is the foundation of cross‐reactivity among different arthropod species. The high homology in the sequence is up to 98% among crustacean TMs, and 68%−100% among molluskan TMs (Duan et al., 2021; Palmer et al., 2020; Prester, 2016). Similarly, the high homology in the sequence is 80%−97% among crustaceans and house dust mite TMs and 78%−98% among crustacean and cockroach TMs.…”
Section: Tm: Molecular Characterization Epitopes and Cross‐reactivitymentioning
confidence: 99%
“…A longitudinal study from 18 major cities in China showed that the self-reported prevalence of AR in adults increased by 6.5% in 6 years [ 4 ]. Mugwort and house dust mites are the two most commonly inhaled allergens in Asia [ 5 ]. In North China, more than 50% of individuals with respiratory allergy are allergic to Artemisia pollen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%